Instructional writing in English, 1350-1650 materiality and meaning - Griffin, Carrie 1977- (Routledge, 2019)
"Exploring the nature of practical or instructional works in English transmitted from the later Middle Ages to c. 1650, this volume considers textual and material strategies for the presentation and organisation of written knowledge and information during the period. The volume examines textual and material conditions of such works in manuscript, tracing their development through and beyond the arrival of the printing press in England in the late fifteenth century. Works on surgery, courtesy, astrology, writing for women and codicological recipes are examined closely from the perspective of frameworks, conventions, and structures, and more broadly in terms of transmission and dissemination, attitudes and traditions, readers and audiences, and shifting ideas about knowledge and the professional realm. 'Instructional Writing in English' makes a significant contribution to the study of so-called non-literary textual genres and their transmission, circulation and reception, in manuscript and in early modern printed books"--
Keywords: Didactic literature, English / History and criticism; English prose literature / Middle English, 1100-1500 / History and criticism; English prose literature / Early modern, 1500-1700 / History and criticism